2015
DOI: 10.13053/rcs-95-1-11
|View full text |Cite
|
Sign up to set email alerts
|

Uso de técnicas de agrupamiento en la clasificación de estilos de aprendizaje

Abstract: Resumen. El presente trabajo muestra la utilización de k-means y Fuzzy c-means para la determinación de estilos de aprendizaje en escuelas de educación básica, esto con el fin de establecer estrategias de enseñanza acordes con los perfiles de los alumnos. Dicho análisis de perfiles se basa en el modelo de programación neuro-lingüistica que divide a los estilos en tres, dependiendo de la forma en que favorecen la manera de percibir su entorno.Palabras clave: algoritmos de agrupamiento, teoría neuro-lingüistica,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In this sense the visualization of the multivariate data plays an important role in the fulfillment of the objectives [5]. Some studies in the educational area use graphical visualization techniques such as radar charts to make comparisons that are easy to interpret [6,7]; In other studies, on university academic performance and the aspects that affect it, data analysis techniques have been applied [8,9] or techniques of evaluation of results obtained [10].…”
Section: Multivariate Analysismentioning
confidence: 99%
“…In this sense the visualization of the multivariate data plays an important role in the fulfillment of the objectives [5]. Some studies in the educational area use graphical visualization techniques such as radar charts to make comparisons that are easy to interpret [6,7]; In other studies, on university academic performance and the aspects that affect it, data analysis techniques have been applied [8,9] or techniques of evaluation of results obtained [10].…”
Section: Multivariate Analysismentioning
confidence: 99%
“…There are some works where graphic representations have been developed to know the behavior of the data in educational areas at the license level, such as radar graphs where it is possible to visualize the comparison of the data in a fast way, facilitating the interpretation of the data through colored lines that form polygons [5,6]. Likewise, research has been found related to academic performance and the elements that influence university students where data analysis techniques have been applied [7,8] or techniques for evaluating the results obtained [9].…”
Section: Introductionmentioning
confidence: 99%
“…Research has been found where different techniques of data analysis have been used to obtain information about the academic performance of university students, such as knowing the factors that cause students to desertion through the use of decision trees [7], the use of techniques of grouping to know the styles of learning [8], among others. Some research involves the personal factor with academic performance, data have been obtained from formal surveys, which have been applied data analysis techniques to discover the relationships between the variables involved, such as rules of association techniques [9], Classification techniques such as trees [10]. There are currently a large variety of studies based on the use of principal components where observations are presented on the axes formed by the first two main components [11].…”
Section: Introductionmentioning
confidence: 99%